Um estudo sobre as ATPCS em são Paulo: EFAPE e a formação continuada de professores de química - Diniz, Vanessa Mota (2024)
The study examines the continuing education of Chemistry teachers within the context of EFAPE, focusing on the Collective Pedagogical Work Activities (ATPCs). It analyzes the impact of centralizing and technocratic educational policies on teachers' professional development, emphasizing the standardization of practices and the limitation of teacher autonomy. The research follows a qualitative approach, combining document analysis, literature review, and participant research. Official documents, formative guidelines, and teaching materials provided by EFAPE were analyzed, along with interviews with professionals involved in the design and implementation of the ATPCs, as well as observations of these same activities. The Prisma methodology was used for a systematic review of literature in major academic databases. The collected data were organized and interpreted based on the theories of Michael Apple, José Gimeno Sacristán, and Libâneo, providing the theoretical framework for a critical analysis of the formative practices. Results show that EFAPE's continuing education program is characterized by a technocratic and centralized approach, prioritizing standardization and control over teaching practices. The centralization of decisions at EFAPE and the use of a standardized curriculum reflect the subordination of education to market interests, with a pragmatic training organization: pre-molded content with little reflection. This results in a training process that limits teachers' autonomy and facilitates the development of a reproductive pedagogical practice. The analysis also reveals a disconnection between the prescribed curriculum and the local realities of schools, compromising the effectiveness of teachers' professional development. In Chemistry, teacher training follows a technical rationality where practice is treated as a rigid application of predefined techniques and approaches, thus neglecting the diverse realities and needs of the Paulista education system